The influence of environmental engagement in the decision to purchase sustainable cosmetics: An analysis using the Theory of Planned Behavior - Gonçalves, Jaqueline; Santos, Aline Regina; Kieling, Ana Paula; Tezza, Rafael (Revista de Administração da UFSM, 2022)
Purpose: This research aims to identify the influence of environmental engagement on the purchase intention for sustainable cosmetics by Brazilian consumers using the Theory of Planned Behavior. Methodology: In the qualitative phase, the study conducted two in-depth interviews, aiming to build a survey considering the main behavioral, normative, and control consumer beliefs. In the quantitative phase, an online survey was conducted. We analyzed 114 responses from sustainable cosmetics consumers, using SEM. Findings: The results revealed a correlation between purchase intention, consumer attitude, and perceived behavioral control. Although the perceived behavioral control was considered significant, it has a small influence when compared to the individual’s attitude toward the behavior. This means that the stronger the advantages and benefits of using the product, the more likely the consumer is to buy and use it. Also, environmental engagement was proven to positively influence consumer behavioral and normative beliefs. It indicates that the more environmentally engaged the consumer, the greater the advantages the individual perceives in buying sustainable cosmetics. Theoretical contributions: The study extends the theory by determining a model with a significant ability to explain the environmental engagement in sustainable cosmetics’ purchase intention. Regarding consumer behavior, this research has shown that personal feelings are the main influencer of purchase. Relevance/Originality: The increase in sustainable consumption has attracted the attention of the most diverse market segments. This study brings light to new propositions concerning purchase intention and environmental engagement by proposing, testing, and validating a model in the context of sustainable cosmetics.